Study Protocol: A Randomized Controlled Prospective Single-Center Feasibility Study of Rheopheresis for Raynaud’s Syndrome and Digital Ulcers in Systemic Sclerosis (RHEACT Study) - Rademacher, Jan-Gerd; Tampe, Björn; Borisch, Angela; Buschfort, Rosa Marie; von Figura, Andrea; Asendorf, Thomas; Korsten, Peter (Frontiers in Medicine, 2022)
Introduction Raynaud’s phenomenon (RP) and digital ulcers (DU) are frequent manifestations of Systemic Sclerosis (SSc). Despite being very common in SSc patients, both conditions have proven to be notoriously difficult to study. There are very few available approved drugs with varying efficacy. It has been shown that the presence of DU is associated with increased whole blood viscosity (WBV). Rheopheresis (RheoP) is an extracorporeal apheresis technique used to treat microcirculatory disorders by improving blood viscosity. Improved blood flow and wound healing after RheoP treatments have been reported in single case reports. Methods and Analysis We report the clinical trial protocol of “A randomized controlled prospective single-center feasibility study of Rheopheresis for Raynaud’s syndrome and Digital Ulcers in Systemic Sclerosis (RHEACT).” RHEACT aims to investigate the efficacy of RheoP on the Raynaud Condition Score (RCS) as the primary efficacy outcome measure after 16 weeks from baseline. Thirty patients will be randomized in a 1:1:1 ratio to one of two RheoP treatment groups or assigned to the standard of care (SoC) control group (intravenous iloprost). Secondary endpoints include changes in DU, changes in nailfold video capillaroscopy and patient-reported-outcomes (Scleroderma Health Assessment Questionnaire, FACIT-Fatigue, and the Disability of Arm, Shoulder, and Hand, quick version). Discussion Apheresis techniques have been investigated in SSc but mainly in observational, retrospective studies, or single case reports. RheoP is a pathophysiologically driven potential new therapy for heavily burdened patients with SSc-associated secondary RP with or without DU. Ethics and Dissemination The study was registered at clinicaltrials.gov (Identifier: NCT05204784). Furthermore, the study is made publicly available on the website of the German network of Systemic Sclerosis “Deutsches Netzwerk Systemische Sklerodermie (DNSS).”